Driver Drowsiness Detection System - Ranjitha, M.M.; Ushasree, R.; Chitra, B. (INTI International University, 2024)
Among the leading causes of fatalities in traffic accidents is being sleepy while driving. Long-haul truck drivers, bus or overnight bus drivers, and drivers who operate their cars after midnight are more prone to encounter this issue. Accidents Senger’s worst Every year, car accidents involving drunk drivers result in several fatalities and serious injuries. Due to their enormous practical significance, identifying driver tiredness and its indication are therefore significant study areas. The acquisition system, processing system, and warning system are the three components or modules that make up the fundamental sleepiness detecting apparatus. The acquisition system takes a frontal facial video of the driver's and transmits it to the processing block for real-time analysis to identify weariness.